Impact of Antiepileptic Drugs on Cognition and Neuromagnetic Activity in Childhood Epilepsy With Centrotemporal Spikes: A Magnetoencephalography Study - Niu, Kai; Li, Yihan; Zhang, Tingting; Sun, Jintao; Sun, Yulei; Shu, Mingzhu; Wang, Pengfei; Zhang, Ke; Chen, Qiqi; Wang, Xiaoshan (Frontiers in Human Neuroscience, 2021)
Objective: Childhood epilepsy with centrotemporal spikes (CECTS), the most common childhood epilepsy, still lacks longitudinal imaging studies involving antiepileptic drugs (AEDs). In order to examine the effect of AEDs on cognition and brain activity. We investigated the neuromagnetic activities and cognitive profile in children with CECTS before and after one year of treatment. Methods: Fifteen children with CECTS aged 6–12 years underwent high-sampling magnetoencephalography recordings before treatment and at one year after treatment, and 12 completed the cognitive assessment (The Wechsler Intelligence Scale for Children). Next, magnetic source location and functional connectivity (FC) were investigated in order to characterize interictal neuromagnetic activity in the seven frequency sub-bands, including: delta (1–4Hz), theta (4–8Hz), alpha (8–12Hz), beta (12–30Hz), gamma (30–80Hz), ripple (80–250Hz), and fast ripple (250–500Hz). Results: After one year of treatment, children with CECTS had increased scores on full-scale intelligence quotient, verbal comprehension index and perceptual reasoning index. Alterations of neural activity occurred in specific frequency bands. Source location, in the 30–80Hz frequency band, was significantly increased in the posterior cingulate cortex (PCC) after treatment. Moreover, FC analysis demonstrated that after treatment, the connectivity between the PCC and the medial frontal cortex was enhanced in the 8–12 Hz frequency band. Additionally, the whole-brain network distribution was more dispersed in the 80–250 Hz frequency band. Conclusions: Intrinsic neural activity has frequency-dependent characteristic. AEDs have impact on regional activity and FC of the default mode network (DMN). Normalization of aberrant DMN in children with CECTS after treatment is likely the reason for improvement of cognitive function.